The management system of dairy buffalo farms in Peninsular Malaysia - Samad, Fadzlin Afiqah A.; Nor, Norhariani Mohd; Azmi, Muhammad Redzuan; Hassim, Hasliza Abu; Buda, Mark; Bakar, Md Zuki Abu; Salleh, Annas; Saad, Mohd Zamri (Asian Journal of Dairy and Food Research, 2024)
Background: In Malaysia, there has not been enough the research on the cost of producing buffalo milk and the in different management system and insight into the industry’s current state is inadequate. This study aims to determine the cost of dairy buffalo milk in selected regions of Peninsular Malaysia Methods: A survey was conducted on 14 dairy buffalo farms from selected regions in Peninsular Malaysia: Selangor (six farms), Kedah (four farms), Penang (three farms) and Pahang (one farm) using a developed questionnaire. The questionnaire consists of farm management aspects like the socio-economics of the farmers, nutrition management, health management, dairy production management and the calculation of the production cost. The collected data were edited in Excel and analysed descriptively using IBM SPSS Statistics. Result: Based on the surveyed, The net profit was RM79,444.56, RM1,924,24.82 and RM2,220,519.02 in traditional, semi-commercial and commercial farms, respectively. This study reveals that milk costs are lowest at commercial farms, indicating the efficiency of farms. When more output is produced, the cost per production unit is reduced. Hence, the government should initiate and encourage the farmers to expand their farm business from traditional to commercial business and, at the same time, produce more skilful farmers.